Exploring the lived experiences of highly successful low socio-economic background students from community day secondary school in Malawi’s higher education - Sinthampi-Banda, Tiffany Vincentia (My University, 2020)
Policies to widen access in higher education have been extensively adopted globally, with the aim of targeting a wider population and being inclusive of those considered marginalised, among whom are those from low socio-economic backgrounds. Despite the efforts of inclusion of the marginalised into the system, they persistently fall through, in what Dawes, Yeld and Smith (1999, p.97) term the ‘revolving door syndrome’. This, as the targeted students, who gain access into higher education, fail to obtain the intended results, due to high dropout and low throughput. While the academic legacy of students, from a low socio-economic background, in higher education has been characterised by high dropout, low throughput and incompletion, there have been pockets of students from this background that have defied the odds to show academic excellence in higher education. Little is known of these students. Using a qualitative research approach, this study adopted a phenomenological case study research design to explore the lived experiences of highly successful students from a low socio- economic background, in Malawi’s higher education. Data collected, through individual interviews and shadowing, explored their experiences as students in a higher education institution, as well as their perception of the role of the institution regarding their lives as students from the specific type of background. Finally, data on the perceived non-institutional mediating factors in their success was also collected. The study found that these respondents, just like literature explains, lacked necessary capitals that would enhance their academic attainment. Their lived experiences revealed resource constraints, compromised educational foundation, stigmatisation and lack of institutional support, as some of the challenges they encountered. Despite these challenges, some mediating factors acted as enablers in their ability to beat the odds and exhibit academic excellence. From the analysis of data, themes emerged that explained the constraining experiences of students from a low socio-economic background, including the captivity that came with their background; the challenges of overcoming barriers, that they encountered by virtue of their background; and the systemic gaps at the policy and institutional levels. Beyond these constraining experiences, data revealed opportunities that students exploited in mitigating the constraining experiences. Themes falling under these opportunities included personal initiatives, family/community resilience, peer safety net and institutional intervention. It can, therefore, be argued that, in order to address the academic plight of students from a low socio- economic background, effort needs to be made to strengthen these mediating factors, which, among others, calls for institutions to harness. One of the contributions of this study was the ‘Success Against Odds’ (SAO) model that brings together all these themes into a coherent way of understanding both the plight of students from a low socio-economic background and as the mediating factors that explain their ability to beat the odds and succeed academically. As a contribution, this model would be used as a tool to explore this research area further, especially when relating to the context of less developed countries, where most of the theories that explain this phenomenon from the developed countries’ contexts were found to be lacking.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Wits School of Education, Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2020